Green Supply Chain Decisions and Revenue-Sharing Contracts under Manufacturers’ Overconfidence - Hui Zhou; Lu Liu; Weifan Jiang; Shengsheng Li (Journal of Mathematics)
Overconfidence is a prevalent and potentially catastrophic behaviour in judgment and decision-making. In this paper, we define manufacturers’ overconfidence as a belief bias that they overestimate the impact of product greenness on demand and the accuracy of demand uncertainty. We build a game theory model based on overconfident beliefs, address the decisions of product greenness and price, and discuss the impact of manufacturers’ overconfidence on supply chain decisions and profits. For the adverse effects brought by overconfidence, we further investigate whether revenue-sharing contracts can coordinate green supply chains. We find three new insights. (1) Manufacturers’ overconfidence leads to higher product greenness, a higher wholesale price, and a greater retail price, but resulting in lower profits. (2) Under the cooperation based on revenue-sharing contracts, product greenness is greater, and wholesale price is lower than the case without cooperation. The greenness increases with the manufacturer’s overconfidence, but counter-intuitively, the wholesale price is not affected by overconfidence. (3) Both the overconfident manufacturer and the retailer have an incentive to reach a revenue-sharing contract. Retailers benefit from collaboration, and overconfident manufacturers assume that retailers can make more profit through revenue sharing, but this model does not exist.